Heaven official's blessing = Tian guan ci fu. 8 - Moxiangtongxiu (Seven Seas Entertainment, 2023)
"White No-Face's mask is off, and the final conflict has begun. Deep in the ancient caverns and lava flows of Mount Tonglu, Xie Lian must face the one whose hatred has plagued him for centuries--but this time, he won't have to do it alone. His beloved, Hua Cheng, has spent his long existence amassing the power to protect him, and now with their feelings for each other out in the open, they have all the more reason to fight for survival"--